Lysosomal membrane protein SIDT2 mediates the direct uptake of DNA by lysosomes. Issue 1 (2nd January 2017) - Aizawa, Shu; Contu, Viorica Raluca; Fujiwara, Yuuki; Hase, Katsunori; Kikuchi, Hisae; Kabuta, Chihana; Wada, Keiji; Kabuta, Tomohiro
ABSTRACT: Lysosomes degrade macromolecules such as proteins and nucleic acids. We previously identified 2 novel types of autophagy, RNautophagy and DNautophagy, where lysosomes directly take up RNA and DNA, in an ATP-dependent manner, for degradation. We have also reported that SIDT2 (SID1 transmembrane family, member 2), an ortholog of the Caenorhabditis elegans putative RNA transporter SID-1 (systemic RNA interference defective-1), mediates RNA translocation during RNautophagy. In this addendum, we report that SIDT2 also mediates DNA translocation in the process of DNautophagy. These findings help elucidate the mechanisms underlying the direct uptake of nucleic acids by lysosomes and the physiological functions of DNautophagy.